Fiscal Sustainability and Demographic Change: A Micro Approach for 27 EU Countries - Mathias Dolls; Karina Doorley; Alari Paulus; Hilmar Schneider; Sebastian Siegloch; Eric Sommer (Institute for the Study of Labor (IZA), 2015)
The effect of demographic change on the labor force and on fiscal revenues is topical in light of potential pension shortfalls. This paper evaluates the effect of demographic changes between 2010 and 2030 on labor force participation and government budgets in the EU-27. Our analysis involves the incorporation of population projections, and an explicit modeling of the supply and demand side of the labor market. Our approach overcomes a key shortcoming of most existing studies that focus only on labor supply when assessing the effects of policy reforms. Ignoring wage reactions greatly understates the increase in fiscal revenues, suggesting that fiscal strain from demographic change might be less severe than currently perceived. Finally, as a policy response to demographic change and worsening fiscal budgets, we simulate the increase in the statutory retirement age. Our policy simulations confirm that raising the statutory retirement age can balance fiscal budgets in the long run.
Keywords: H68; J11; J21; 330; demographic change; fiscal effects; labor supply; labor demand; pension systems